Complementary Feeding Practices and Child Growth in a Region with a High Burden of Child Undernutrition in Madagascar. (29th May 2020) - Rakotomanana, Hasina; Hildebrand, Deana; Gates, Gail; Thomas, David; Stoecker, Barbara
Abstract: Objectives: The Vakinankaratra region of Madagascar has the highest stunting rates of the country, yet it is one of most agriculturally productive regions. The purpose of this study was to assess maternal complementary feeding practices and their association with child growth. Methods: Data from a cross-sectional study of 391 mothers and their infants aged 6–23 months were analyzed. The WHO infant and young child feeding (IYCF) indicators were used to assess complementary feeding practices. A questionnaire for collection of sociodemographic information and 24-hour dietary recall was translated and pre-tested before data collection. Child length and weight were converted to length-for-age (LAZ), weight-for-age (WAZ), and weight-for-length (WLZ) using the 2006 WHO Growth Standards. Linear regression models were conducted while adjusting for survey design and confounding variables. Results: Stunting (69.4%) and undernutrition (23.4%) rates were very high. The proportion of children achieving minimum dietary diversity (35.8%), minimum acceptable diet (30.2%) and consuming flesh foods (14.1%) were low. Higher dietary diversity score was associated with increased LAZ [β = 0.2, P < 0.05, R 2 = 0.16] in 9–11 months infants only. Consuming flesh foods was associated only with higher WAZ [β = 0.41, P < 0.01, R, 2 = 0.10]. None of the indicators were associated with WLZ. Conclusions: Complementary feeding practices were suboptimal in the Vakinankaratra region. Although crucial for optimal growth, improving feeding practices alone may not be sufficient to reduce the high prevalence of child undernutrition in the region. Funding Sources: This study was funded by the Marilynn Thoma Chair in Human Sciences at Oklahoma State University.